2015
DOI: 10.12693/aphyspola.128.240
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Viscosity of Aluminum Oxide-Ethylene Glycol (Al₂O₃-EG) Nanofluids

Abstract: The paper presents the results of measurements of rheological properties of ethylene glycol (EG) based aluminum oxide (Al2O3) nanouids. The nanouids have been produced by two-step method with the use of commercially available nanoparticles. Dynamic viscosity curves and dependence of viscosity on temperature for these materials have been measured. It has shown that with higher concentration of nanoparticles in the suspension, these nanouids exhibit the non-Newtonian ow and it can be considered as shear-thinning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
4
4
0
Order By: Relevance
“…Moreover, the viscosity of ILs-based nanofluids increased with the SiC loading for the whole temperature range, which can be attributed to the nanoparticles' aggregation. For example, in the case of 0.06 wt% of SiC loaded IL, the viscosity increased by nearly 15.6% at 25 • C. A similar effect of nanoparticles loading on viscosity of ILs was also reported by Saidur et al and Zyla et al [93,94]. dominates the thermal conduction of the ionanofluid at low temperatures.…”
Section: Viscositysupporting
confidence: 79%
“…Moreover, the viscosity of ILs-based nanofluids increased with the SiC loading for the whole temperature range, which can be attributed to the nanoparticles' aggregation. For example, in the case of 0.06 wt% of SiC loaded IL, the viscosity increased by nearly 15.6% at 25 • C. A similar effect of nanoparticles loading on viscosity of ILs was also reported by Saidur et al and Zyla et al [93,94]. dominates the thermal conduction of the ionanofluid at low temperatures.…”
Section: Viscositysupporting
confidence: 79%
“…Their results indicated that their nanofluids were Newtonian. On the other hand, some researchers such as Żyła et al [32,33], Li et al [35], Mariano et al [34] and Li et al [35] observed non-Newtonian behaviour of Al2O3, AlN, SnO2, SiC nanoparticles dispersed in ethylene glycol.…”
Section: Introductionmentioning
confidence: 98%
“…However, when planning the practical use of nanofluids, it should be taken into account that with increasing concentration of the nanoparticles in a liquid its viscosity increases [19,20,26]. In some cases, an increase in viscosity may also be associated with a change of liquid from Newtonian to non-Newtonian [27][28][29][30][31][32][33]. It was also demonstrated that the addition of nanoparticles changes the electrical properties of ethylene glycol [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%